The Favela of Batan and the UPPs’ project: the evaluation of the residents about their experience with permanent police occupation - Dias, Ariley Pinto Rainho (2017)
The favela of Batan, located in west zone of Rio de Janeiro`s city, was one of first territories to receive Pacifying Police Units (UPPs) – a project that aims the permanent police occupation in areas considered dangerous in the city and it offers a counterpart new public goods and services to people from occupied areas. This article result from an ethnographic research began in 2014 and ended in 2016. I propose to analyze the residents` evaluation about the impacts of this public policy in their everyday life and their effects in their perception about the future of this site. The data shows the disappointment of residents not only in relation to project but due to incapacity of State to resolves their problems. The residents started to believe in inability of social projects in transform those who are considered “irrecoverable”.